Diseño del sistema de alcantarillado combinado del barrio El Guabo. - Martínez Pozo, Raúl Arnulfo (2006)
The purpose of this thesis is to contribute to basic sanitation, such as the combined sewer system in the neighborhood of El Guabo, the Monjas sector, and the fulfillment of the prerequisite for obtaining a Civil Engineer. Every development plan is largely based on the average sanitation that includes the preservation and conservation of the ecology that will be of direct benefit to society, contributing to their future well-being. Sanitation encompasses many activities, among which the most important, and which are related to urban development, are sewage systems and the control of environmental pollution.